If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5x+36=12x+1
We move all terms to the left:
5x+36-(12x+1)=0
We get rid of parentheses
5x-12x-1+36=0
We add all the numbers together, and all the variables
-7x+35=0
We move all terms containing x to the left, all other terms to the right
-7x=-35
x=-35/-7
x=+5
| 4(6x–7)=144 | | 4(m+2)=6m-3 | | 3x-11=3x-1 | | 8x-37=3x-7 | | 3(x-5)=7+12 | | 2x−1=4x+2 | | 3-2x=0,333333333333333333333333333333333(x+2) | | -5+4g+g=10 | | 3-2x=0,33(x+2) | | 3-2x=(1/3)(x+2) | | -24.4b=14.4 | | 18-4a=5a | | -2x-4=3x+31 | | 5z+6=–9 | | 2(x-2)=6-3(x+5) | | 2(4x+5)=2x+4 | | 3=20+4c | | 8c+3c=2c-5c | | 8(5^(x+3))–54=146 | | 3d-d=2d+4d | | 10/4=n/8 | | 3y+4=y+4 | | 3x4=-12 | | 3k+3k+k-6k=1 | | 7x+9x=3x+2x | | 11g+2g-12g=9 | | 19z+4z-20z-2z=13 | | 5(4x-4)-19x=4 | | 3/6=4n | | 17h-16h=10h | | 5(2x-3)=2(x+2)+2(2x-1)-7 | | m+(8/m)=6 |